Comparative evaluation of manual and robotic grafting in brinjal (Solanum melongena L.) - Motapalukula, Jyothi; Gopal, U Shinde; Tambe, T B (Plant Science Today, 2025)
The proposed research work introduces robotic and manual grafting methods of eggplant seedlings of same genetic characteristics with their keen observative comparisons for precision and optimum production. The manual and mechanical grafting process using a semi-automated ultra precision grafting robot AFGR-800CS. These experiments were conducted at NAHEP-CAAST-DFSRDA under Agri-bot division in 2021 in collaboration with College of Agriculture, Department of Horticulture, VNMKV, Parbhani (Maharashtra) for varieties of brinjal such as Krishna, Phule Arjun, Manjari Gota and Phule Harit. The purpose of the comparative evaluation is to observe an impact of automation technology in comparison with manual method for Solanum torvum and arranged in a CRBD (Completely Randomised Block Design). Considerable differences were identified in the experimental results for the many attributes. The lowest days for healing (4.258 days) with the highest grafting success (96.285 %) and leaf count per plant (6.503) detected in Phule Arjun joined on Solanum torvum using robotic grafting technique. The least days to emergent was noted for Krishna (6.705 days) attached on Solanum torvum through robotic technique. While, the supreme diameter of rootstock (2.898 mm) and diameter of scion (2.880 mm) noted in Phule Harit joined on Solanum torvum through physical grafting technique. Meaningfully, the highest height of plant (16.225 cm) and grafts per hour (689.50) were noticed in Phule Harit united on Solanum torvum through using robotic attaching technique. Based on the findings, it can be inferred that grafting technology shows a positive effect when Solanum torvum Sw. was used as rootstock.